Experience of using secukinumab in the treatmentof patients with psoriasis - N. V. Zilberberg; Ya. V. Kascheeva; M. M. Kokhan (Лечащий Врач)
Psoriasis is one of the most common chronic dermatoses. In recent years, there has been an increase in the number of patients with severe, disabling forms of dermatosis, resistant to the therapy. The disease significantly reduces the quality of life, disrupts patients' ability to work, which defines dermatosis as socially significant and entails the need to improve therapeutic approaches. Psoriatic arthritis, or artopathic psoriasis, is a chronic inflammatory disease of the joints, spine and enthesis, which can be observed in patients with psoriasis. The article presents the main current information about the pathogenesis of psoriasis and psoriatic arthritis with an emphasis on the immunopathological aspects of the development of diseases and the rationality for the use of the proinflammatory cytokine inhibitor interleukin-17 in the therapy. Modern advances in understanding the mechanism of development of psoriasis and psoriatic arthritis served as a rationale for the creation of a group of innovative targeted drugs – genetically engineered biological drugs, the mechanism of action of which is to block certain cytokines, both circulating in the systemic circulation and located in the inflamed tissue of psoriatic plaques or joint. In the article brief information about the results of clinical trials of secukinumab is provided; clinical examples highlight experience of effective treatment of patients with psoriasis and psoriatic arthritis. It has been shown that early cessation of the progression of the inflammatory process in psoriasis through biological therapy with secukinumab leads to a decrease in skin symptoms, a decrease in pain and subclinical inflammation in the joints. The high efficacy and safety of the drug allows complete control of the disease and improve the quality of life in patients.